The t(8;21) chromosomal translocation in acute myelogenous leukemia modifies intranuclear targeting of the AML1/CBFα2 transcription factor - McNeil, Sandra (The National Academy of Sciences, 1999)
Targeting of gene regulatory factors to specific intranuclear sites may be critical for the accurate control of gene expression. The acute myelogenous leukemia 8;21 (AML1/ETO) fusion protein is encoded by a rearranged gene created by the ETO chromosomal translocation. This protein lacks the nuclear matrix-targeting signal that directs the AML1 protein to appropriate gene regulatory sites within the nucleus. Here we report that substitution of the chromosome 8-derived ETO protein for the multifunctional C terminus of AML1 precludes targeting of the factor to AML1 subnuclear domains. Instead, the AML1/ETO fusion protein is redirected by the ETO component to alternate nuclear matrix-associated foci. Our results link the ETO chromosomal translocation in AML with modifications in the intranuclear trafficking of the key hematopoietic regulatory factor, AML1. We conclude that misrouting of gene regulatory factors as a consequence of chromosomal translocations is an important characteristic of acute leukemias.